EASTERN DIRECTION OF THE RUSSIAN FOREIGN POLICY AT THE TURN OF XVIII-XIX CENTURIES: THE GEO-ECONOMIC AND GEOPOLITICAL ASPECTS - М.С., Мырзaбеков; Р.С., Мырзaбековa; Г.К., Кокебaевa (Journal of Oriental Studies, 2019)
The article shows the main stages, trends, objectives and tasks of the eastern direction in Russian foreign policy at XVIII-XIX centuries. Its place and role in the international relations, participation in solv- ing the major international problems, mechanisms and development factors, causes and changes effects in the world politics are discussed, as well as the impact of these processes on the competition among Great Britain and Russia in Central Asia. The article also reveals the causes and circumstances of the Anglo-Russian rivalry and the main stages of the development of relations between Britain and Russia in the second half of the XIX century. Key words: Sweden, Turkey, England, Russia, Central Asia, rivalries, colonialism, geopolitics.